Quality Assurance in Southeast Asia’s Higher Education: Some Lessons for Africa? - (:unkn) unknown (My University, 2024)
Most countries have quality assurance (QA) systems in place to monitor and improve their educational policies. Typically, such systems aim at enhancing transparency, assessing performance, and providing appropriate guidelines for forward-looking practices. Higher education institutions (HEIs) in developed countries have implemented QA systems that ensure consistent and transparent achievements. The main objective of this study is to analyse and contrast the functioning of quality assurance systems in Southeast Asia and Sub-Saharan Africa. Based on our reading, it elaborates on the pivotal aspect about the efficacy of quality assurance methods in Southeast Asia. Various quality assurance (QA) techniques used in both domains are also examined, along with the issues that arise from these systems. Fundamentally, this paper describes a proposed strategy for exploring a prospective path that can be useful for guiding the development of QA systems in Sub-Saharan Africa.
Keywords: African Research